Structural, Physicochemical, and Functional Properties of Wheat Bran Insoluble Dietary Fiber Modified With Probiotic Fermentation - Liao, Ai-Mei; Zhang, Jie; Yang, Zhen-Lin; Huang, Ji-Hong; Pan, Long; Hou, Yin-Chen; Li, Xiao-Xiao; Zhao, Peng-Hui; Dong, Yu-Qi; Hu, Zhe-Yuan; Hui, Ming (Frontiers in Nutrition, 2022)
Insoluble dietary fiber (IDF) were extracted from wheat bran (WB) after microbial fermentation with single or mixed strain (Lactobacillus plantarum, Lactobacillus acidophilus, Bacillus subtilis or mixed lactic acid bacteria (Lactobacillus plantarum and Lactobacillus acidophilus with ration of 1:1). The structure, physicochemical, functional properties, and antioxidant activity of wheat bran insoluble dietary fiber (W-IDF) modified by fermentation were studied. Fourier transformed infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM) analysis suggested the chemical bond arrangement and structural change of W-IDF after biological modification. After fermentation with Lactobacillus plantarum and mixed lactic acid bacteria, the water retention capacity (WRC), oil retention capacity (ORC), and water swelling capacity (WSC) of W-IDF were improved. The sodium cholate adsorption capacity (SCAC), and cation exchange capacity (CEC) of W-IDF modified with Lactobacillus acidophilus fermentation were significantly increased. Although the cholesterol adsorption capacity (CAC) of W-IDF decreased after probiotic fermentation modification, nitrite ion adsorption capacity (NIAC), and total phenol content (TPC) were enhanced. Additionally, W-IDF modified by fermentation with Bacillus subtilis or mixed lactic acid bacteria exhibited superior antioxidant capacity verified by DPPH, ABTS and total reducing power assays. The results manifested that microbial fermentation is a promising methods to modify the W-IDF to provide high-quality functional IDF for food processing and human health management.